Surface Modification of V–VI Semiconductors Using Exchange Reactions within ALD Half-Cycles - Wiegand, Christoph W.; Zierold, Robert; Faust, Rene; Pohl, Darius; Thomas, Andy; Rellinghaus, Bernd; Nielsch, Kornelius (Advanced Materials Interfaces, 2018)
The behaviors of tellurium and selenium atomic layer deposition vapor precursors, namely, Te(SiEt3)2 and Se(SiEt3)2, exposed to different V–VI semiconductor surfaces are reported. The interactions of the precursors with the substrates are monitored in situ with a quartz crystal microbalance (QCM) setup. Specifically, both the utilized metal–organic precursors interact with chalcogenide surfaces but differ in their reaction behaviors. Indeed, exchanged Te diffuses into the selenium-containing substrate, whereas Se only exchanges with the top surface of the substrate. Transmission electron micrsocopy (TEM) and energy-dispersive X-ray spectroscopy (EDX/EDXS) analysis of the topological insulating nanowires reveals the single precursor interactions, which support the QCM data analysis, and provides insight into the morphological and crystalline structures of the altered substrates.
CRIS-Team Scopus Importer:2022-04-14
Keywords: atomic layer deposition; exchange reactions; quartz crystal microbalance; topological insulator